Broad ligament pregnancy a diagnostic dilemma: a case report - Gupta, Amit; Mahajan, Neelam; Verma, Divya; Sharma, Chanderdeep; Rattan, Amit; Gupta, Bharti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Broad ligament pregnancy is one of the rarest forms of ectopic pregnancy with high risk of maternal mortality. Although ultrasonography is usually helpful in making the diagnosis but it is mostly established during laparotomy. 34 year old G2P1 with previous caesarean section reported at 8th month of pregnancy with inability to perceive foetal movements. Ultrasonography confirmed intrauterine fetal demise. Patient was taken for caesarean section after failed induction. Intraoperative diagnosis of broad ligament pregnancy was made and broad ligament along with fetus, sac, fallopian tube and ovary was excised. Post-operative period was uneventful.